PENGAKUAN PERSEDIAAN BARANG CACAT DAN RUSAK PADA PEDAGANG SAYUR DAN BUAH ANTAR PULAU DI PELABUHAN WANI - Sri Hardianti; Jurana Jurana (Universitas Bunda Mulia, 2017)
This study aims to determine what kind of treatment of defective products and defective inventory on vegetable and fruit traders in the port Wani . By using qualitative methods , the research done by observation and in-depth interviews on informants who have been determined by 4 people . With research sites Wani port Jl . H. Ambo District of Edo Village Wani two Tanantovea Donggala . The results of this study indicate that they are not doing the treatment of defective products . Where , no restoration they did based on the theory that a defective product is a product that failed technically and economically still be improved into a product that is in accordance with the defined quality standards but requires an additional charge . In this effort they are explained in the treatment of defective products . Treatment and they do the calculations included in the calculation and accounting treatment , which is normally defective product , sold. By treating the sale of defective products as a reduction of cost of finished products . Going forward , traders expected the inter- island vegetables and fruits can implement a complete accounting records and financial management in more detail in order to be more organized . Where any amount of goods entering recorded and classified the number of defective items and damaged so that lossesOr gains that could be obtained in prediction . Keyword: Inventory , defective products and defective